Resilience Among Breast Cancer Survivors of Different Sexual Orientations - Bazzi, Angela R. (LGBT Health, 2018)
Purpose: Resilience could help protect the psychosocial wellbeing of sexual minority women (SMW) experiencing stressors from both breast cancer and sexual minority status; however, little research has assessed resilience among breast cancer survivors of different sexual orientations. Methods: From 2011 to 2012, we surveyed a national sample of breast cancer survivors matched on sexual orientation, age, and cancer status. Results: Among heterosexual (n = 339) and sexual minority (n = 201) breast cancer survivors (n = 540 overall), multivariable regression analyses revealed that more social support (coefficient: 0.87; 95% confidence interval [CI]: 0.56–1.19), fighting spirit combined with helplessness/hopelessness (coefficient: 0.30; 95% CI: 0.13–0.47), and fatalism (coefficient: 0.40; 95% CI: 0.14–0.65) were associated with greater resilience. Mental health counseling before breast cancer diagnosis and anxious preoccupation following cancer diagnosis were associated with reduced resilience (coefficient: −2.50; 95% CI: −3.83 to −1.18; and −0.46; 95% CI: −0.60 to −0.32). Although sexual orientation was not independently associated with resilience, among SMW, those who were unemployed had reduced resilience compared with those who were employed (coefficient: −3.52; 95% CI: −5.75 to −1.28), whereas there was no association between employment and resilience among heterosexual women. Conclusion: These findings suggest that social support and other factors associated with resilience could be leveraged by interventions to improve the health and wellbeing of diverse cancer survivors.